Assessment of stress and health conditions among students in the context of the war in Ukraine - Vladimir Potop; Igor Vypasniak; Iryna Ivanyshyn; Vasyl Lutskyi; Iryna Kryventsova; Lyudmila Shesterova; Katarzyna Prusik (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. In the context of a military conflict, students’ health is subjected to significant stress and psychological challenges. Monitoring the health condition of this vulnerable group can provide important data for developing effective support measures. The aim of this study is to assess the level of stress and health condition of students in Ukraine during the war and to compare these indicators with those of students from neighbouring countries, Poland and Romania.